Scope of family in public health: An epidemiologist's perspective - Saurabh R Shrivastava; Prateek S Shrivastava; Jegadeesh Ramasamy (Wolters Kluwer Medknow Publications, 2015)
The family is a primary unit in all the societies and is the crucial element around which health services are developed by the program managers. Prevention of disease and bringing improvement in the health conditions in any society is dependent upon the ability of the public health professionals to understand and improve the social or environmental factors. The family plays an important part in maintenance of the optimum level of health and in the dynamics of the disease. In addition, there are multiple functions and responsibilities associated with a family, all of which are relevant to health and health behavior. Realizing the impact of the family on the society and community, all the public health strategies are developed with the aim of appealing to the needs of the family. To conclude, the role of the family in the growth of society is of paramount importance, and thus, program managers should implement measures to ensure harmonization within the family for safeguarding the future of human generations in the years to come.